A munkakereslet nemzetközi tendenciái - Dániel Horn (Hungarian Academy of Sciences, Institute of Economics, 2011)
– The goal of this study is to find the model that best describes the trends in labor demand using international industry level longitudinal data. Our starting point is Kézdi et al. (2006), who uses a fixed-effect model to project labor demand. We take their model and compare it with several other specifications to test forecasting fit. The main conclusions of this study are that different functional forms are better for different industries, but the linear specification fares just fine in all industries. Moreover, fixed-effect models are not better than the simple models with level effects, but results of this latter are easier to interpret. Quasi-autoregressive models do not improve forecasting fit as much as expected.
Keywords: J23; E27; 330; labor-demand; forecasting; industry level panel; Wirtschaftswachstum; Arbeitsnachfrage; Prognose